Facial attraction: an exploratory study of the judgements made by people with intellectual disabilities. Issue 5 (21st February 2021) - Donnachie, M.; Jones, B.; Jahoda, A.
Abstract: Background: Although romantic or sexual attraction is a major research topic in the general population, little is known about people with intellectual disabilities' (ID) views of attractiveness. Methods: Fifty‐eight participants (16–40 years) took part in this exploratory study, 29 with ID and 29 without ID. Participants were shown 50 images of men or women's faces and asked to rate how attractive they thought the faces were. Results: A strong association was found between what men and women with ID and those without ID considered attractive in romantic partners. However, people with ID were more likely to consider themselves desirable to others. Conclusions: The findings suggest that people with mild ID make the same subtle judgements about facial attraction as other individuals.